The easiest way to solve this is by substitution. This means that you set one of the equations equal to a variable and you plug that variable into the variable of the other equation. The second equation (y = 7x) is already set up this way so we will plug it into the first equation.

-5x + 2(7x) = 9

-5x + 14x = 9

9x = 9

(9x)/9 = (9)/9

x = 1

You have found x. Now, plug this number into the second equation (y = 7x) to find the value of y.

## Answers ( )

Answer:x−y

=

9

, x

+

y

=

6

x+

y

=

4 , x

−

y

=

2

x+

2

y

=

4 , x

−

y

=

−

3

try out these examples?Answer:x = 1

y = 7

Step-by-step explanation:Your system of equations is

-5x + 2y = 9

y = 7x

The easiest way to solve this is by substitution. This means that you set one of the equations equal to a variable and you plug that variable into the variable of the other equation. The second equation (y = 7x) is already set up this way so we will plug it into the first equation.

-5x + 2(7x) = 9

-5x + 14x = 9

9x = 9

(9x)/9 = (9)/9

x = 1

You have found x. Now, plug this number into the second equation (y = 7x) to find the value of y.

y = 7(1)

y = 7